'Irlanda, gure bihotzean' (Ireland, in our heart) - Calzada, I (Euskal Editorea SM, 2020)
This article examines the General Elections 2020 outcome in Ireland and analyses political potential effects on issues such as reunification and the Unity Referendum, among others.